Association of Ovary-Sparing Hysterectomy With Ovarian Reserve. Issue 5 (May 2016) - Trabuco, Emanuel C.; Moorman, Patricia G.; Algeciras-Schimnich, Alicia; Weaver, Amy L.; Cliby, William A.
Abstract : OBJECTIVE: To evaluate the association of hysterectomy on ovarian function by comparing antimüllerian hormone, a marker of ovarian reserve, before and after hysterectomy. METHODS: The Prospective Research on Ovarian Function study prospectively followed 1) premenopausal women undergoing ovary-sparing hysterectomy for benign indications, and 2) a referent cohort with similar age distributions and intact reproductive organs; they reported that women undergoing hysterectomy became menopausal 1.9 years earlier than referents. In a planned secondary analysis, baseline antimüllerian hormone levels and the absolute change and percentage change in antimüllerian hormone levels between baseline and 1-year follow-up were compared between groups. RESULTS: Baseline median antimüllerian hormone levels were similar between the hysterectomy group (n=148) and the referent group (n=172). After 1 year, patients undergoing hysterectomy had a significantly greater median percentage decrease (−40.7% compared with −20.9%; P <.001), had a higher proportion with undetectable antimüllerian hormone (12.8% compared with 4.7%; P =.02), and had on average 0.77 times the antimüllerian hormone level ( P =.001) compared with referents. These differences were attenuated among white women but remained significant among black women. Comparisons of women stratified by low or high ovarian reserve at baseline or among propensity score-matched cohorts showed similar findings; however, the absolute median change in antimüllerian hormone levels was similar between groups (−0.3 compared with −0.2; P =.31). CONCLUSION: Women undergoing hysterectomy had similar antimüllerian hormone levels at baseline and experienced a greater percentage decrease in levels after 1 year compared with referents, suggesting that hysterectomy may lead to ovarian damage that is unrelated to baseline ovarian reserve. Abstract : Women with ovary-sparing hysterectomy have a greater percentage decrease in antimüllerian hormone levels after 1 year compared with referent women, suggesting surgery-related ovarian damage.